Demand volatility and the lag between the growth of temporary and permanent employment - Sainan Jin; Yukako Ono; Qinghua Zhang (Federal Reserve Bank of Chicago, 2007)
The growth rate of temporary help service employment is often considered to be a leading business cycle indicator, because the firing and hiring of temporary help workers typically lead that of permanent workers. However, few works in the literature focus on the mechanism that generates the lag between temporary and permanent growth. This paper investigates how demand volatility is related to the lag. Focusing on the relationship between a firm's information extraction and their hiring/firing decisions, our simple model predicts that the average size of transitory demand shocks increase the lag while the average size of shocks that persist longer shortens the lag. Our empirical findings based on cross-city analysis seem to support the above predictions, after controlling for city size, share of good-producing sectors and other city-specific demographic characteristics. In addition, we find that the effect of the size of transitory shocks depends on the degree to which transitory demand shocks of different industries is correlated.
Keywords: J01; R1; 330; temporary help workers; leading business cycle indicator; demand volatility